Electrode position of nickel-cobalt/alumina (Ni-Co/Al2O3) composite coatings: A current approach - Nik Yusoff, N.H. (Asian Research Publishing Network, 2016)
This paper provides a review of the electrode position process that is used to produce nickel-cobalt / alumina (Ni-Co/Al2O3) composite coatings. The electrode position techniques, consisting of direct current, pulse current and pulse reverse current, sediment electrode position, and CO2 bath, are described. The effects of electrode position variables, including applied current density, deposition time, particle concentration and use of surfactants, are also explained. The paper then discusses the limitations of previous studies, such as lack of focus on the effectiveness of this coating in corrosive and erosive environments, and the effects of alumina particles on coating microstructures. It also suggests longer exposure to corrosive media for more significant corrosion study. Further research needs to be conducted in order to improve the corrosion and erosion resistance of Ni-Co/Al2O3 in harsh environments, such as marine conditions. Â© 2006-2016 Asian Research Publishing Network (ARPN).